2008
DOI: 10.1128/aem.02771-07
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Structure and Stability of the Bacterial Community in Belgian Sourdough Ecosystems as Assessed by Culture and Population Fingerprinting

Abstract: A total of 39 traditional sourdoughs were sampled at 11 bakeries located throughout Belgium which were visited twice with a 1-year interval. The taxonomic structure and stability of the bacterial communities occurring in these traditional sourdoughs were assessed using both culture-dependent and cultureindependent methods. A total of 1,194 potential lactic acid bacterium (LAB) isolates were tentatively grouped and identified by repetitive element sequence-based PCR, followed by sequence-based identification us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 33 publications
(61 reference statements)
8
79
0
Order By: Relevance
“…In addition, biases at the level of DNA extraction and PCR specificity and efficiency [9,14,17] could also have played a role. The inability of PCR-DGGE to detect all the bacterial species associated with fermented sorghum was also observed for sourdough [49,71] and whey cultures of water buffalo mozzarella [16]. PCR-DGGE results are also strongly influenced by the intraspecific heterogeneous nature of the 16S rRNA gene region targeted [18,74], which might be the case for putative Pantoea and Enterobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, biases at the level of DNA extraction and PCR specificity and efficiency [9,14,17] could also have played a role. The inability of PCR-DGGE to detect all the bacterial species associated with fermented sorghum was also observed for sourdough [49,71] and whey cultures of water buffalo mozzarella [16]. PCR-DGGE results are also strongly influenced by the intraspecific heterogeneous nature of the 16S rRNA gene region targeted [18,74], which might be the case for putative Pantoea and Enterobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analysis (PCA) using a correlation matrix was carried out to visualize the effects of ingredients and technology parameters on the sourdough microbiotas and the effects of the microbiotas on the biochemical features of the sourdoughs. For each sourdough, a microbial community profile was composed which reflected the qualitative (number of species) and quantitative (number of strains per species) diversity of LAB and yeasts (36). The chemical composition of the flours (concentrations of maltose, glucose, fructose, and total and individual FAA) or other ingredients and microbial community (cell density of LAB and yeasts, number of species, number of strains, and percentages of obligately homofermentative and obligately and facultatively heterofermentative LAB) data were used as variables for PCA analyses.…”
Section: Sourdoughsmentioning
confidence: 99%
“…The chemical composition of the flours (concentrations of maltose, glucose, fructose, and total and individual FAA) or other ingredients and microbial community (cell density of LAB and yeasts, number of species, number of strains, and percentages of obligately homofermentative and obligately and facultatively heterofermentative LAB) data were used as variables for PCA analyses. In addition, microbial community data were also analyzed together with the biochemical characteristics (pH, organic acids, quotient of fermentation, ethanol, and FAA) of sourdoughs (36). All data were standardized before PCA analysis using the statistical software Statistica for Windows.…”
Section: Sourdoughsmentioning
confidence: 99%
“…namely L. rossiae, is being frequently isolated at high numbers from sourdoughs produced in Italy (Valmorri et al, 2006;Di Cagno et al, 2007) and it has been also detected in Belgian sourdoughs (Scheirlinck et al, 2007(Scheirlinck et al, , 2008. The majority of LAB screened and selected to act as starters in sourdough production belong to OHe species (Minervini et al, 2012;Settanni et al, 2013).…”
Section: Strainsmentioning
confidence: 99%
“…Gobbetti (1998) reported on the L. sanfranciscensis/L. plantarum association in Italian wheat sourdough, and Scheirlinck et al (2008Scheirlinck et al ( , 2009 found that the species L. paralimentarius, L. plantarum, L. sanfranciscensis, Lactobacillus pontis and Lactobacillus spicheri were dominant in type I sourdoughs produced in a Belgian bakery. Recently, L. plantarum has been detected at high cell densities, even higher than those of the OHe LAB species, also in Asian sourdoughs (Luangsakul et al, 2009;Zhang et al, 2011), highlighting the relevance of this species to produce sourdoughs throughout the world.…”
Section: Introductionmentioning
confidence: 99%